Novel Intrapolymerization Doped Manganese‐Eumelanin Coordination Nanocomposites with Ultrahigh Relaxivity and Their Application in Tumor Theranostics - Liu, Heng (Adv Sci (Weinh), 2018)
While magnetic resonance imaging contrast agents have potential in noninvasive image‐guided tumor treatment, further developments are needed to increase contrast, biodegradability, and safety. Here, novel engineered manganese‐eumelanin coordination nanocomposites (MnEMNPs) are developed via a facile one‐pot intrapolymerization doping (IPD) approach in aqueous solution, through simple chemical oxidation–polymerization of the 3,4‐dihydroxy‐DL‐phenylalanine precursor with potassium permanganate serving as the Mn source and an oxidant. The resulting MnEMNPs possess ultrahigh longitudinal relaxivity (r (1) value up to 60.8 mM(−1) s(−1) at 1.5 T) attributed to the high manganese doping efficiency (>10%) and geometrically confined conformation. Due to their high manganese chelation stability, excellent biocompatibility, and strong near‐infrared absorption, high‐performance longitudinal‐transverse (T (1) ‐T (2)) dual‐modal magnetic resonance/photoacoustic imaging and photothermal tumor ablation are achieved. Furthermore, the hydrogen peroxide‐triggered decomposition behavior of MnEMNPs circumvents the poor biodegradation issue of many nanomaterials. This facile, convenient, economical, and efficient IPD strategy will open up new avenues for the development of high‐performance multifunctional theranostic nanoplatforms in bionanomedicine.